Patient attitudes towards change in adapted motivational interviewing for substance abuse: a systematic review - Wells SA; Smyth T; Brown TG (Dove Medical Press, 2012)
Samantha Ashley Wells,1,2 Tanya Smyth,1,2 Thomas G Brown1,2,31Department of Psychiatry, Douglas Mental Health University Institute, Montréal, Québec, Canada; 2Department of Psychiatry, McGill University, Montréal, Québec, Canada; 3Foster Addiction Rehabilitation Centre, St. Philippe de Laprairie, Québec, CanadaAbstract: Adapted motivational interviewing (AMI) represents a category of effective, directive and client-centered psychosocial treatments for substance abuse. In AMI, patients’ attitudes towards change are considered critical elements for treatment outcome as well as therapeutic targets for alteration. Despite being a major focus in AMI, the role of attitudes towards change in AMI’s action has yet to be systematically reviewed in substance abuse research. A search of PsycINFO, PUBMED/MEDLINE, and Science Direct databases and a manual search of related article reference lists identified 416 published randomized controlled trials that evaluated AMI’s impact on the reduction of alcohol and drug use. Of those, 54 met the initial inclusion criterion by evaluating AMI’s impact on attitudes towards change and/or testing hypotheses about attitudes towards change as moderators or mediators of outcome. Finally, 19 studies met the methodological quality inclusion criterion based upon a Newcastle-Ottawa Quality Assessment Scale score ≥7. Despite the conceptual importance of attitudes towards change in AMI, the empirical support for their role in AMI is inconclusive. Future research is warranted to investigate both the contextual factors (ie, population studied) as well as deployment characteristics of AMI (ie, counselor characteristics) likely responsible for equivocal findings.Keywords: motivational interviewing, substance abuse, systematic review, readiness to change, self-efficacy